Educational inequalities in self-reported health in a general Iranian population - Goshtasebi Azita; Montazeri Ali; Vahdaninia Mariam (BMC Research Notes, 2008)
Abstract Background The aim of this study was to investigate the relationship between educational level and self-reported health in an Iranian population, in order to provide evidence on social inequalities in health from a country in which such data need to be collected. Methods This population-based study was carried out in Tehran, Iran. Individuals aged 15 years and over were interviewed. Self-reported health was measured by asking each individual to respond to the question: "In general how would you describe your health at present?" We used years of formal education as a measure of socioeconomic status and categorized the answers in five levels. Logistic regression analysis was used to estimate odds ratios and 95% confidence intervals indicating the contribution of educational level to self-reported health, adjusting for age, gender, marital status, and chronic diseases. Results In all, 4163 individuals were interviewed. The mean age of the respondents was 35.1 years (SD = 16.0); 52% were female; the mean duration of formal education was 10.0 years (SD = 4.5); and 31% rated their health 'less than good'. Overall, women rated their health more poorly than men (P < 0.0001), and the findings showed that those with higher education rated their health significantly better than those with lower educational levels after adjusting for the age, gender, marital status and chronic diseases. The odds ratio for having 'less than good' self-rated health in those at the lowest educational level compared with those at the highest was 2.65 (95% CI = 1.88–3.73). Conclusion The findings indicated an inverse relationship between educational level and self-rated health, and that age, gender, and chronic conditions had independent effects on self-reported health status. The findings of this first study from Iran suggest that health inequalities in developing countries such as Iran need to be addressed and policies for tackling the problem should be considered. In this respect, less well-educated people and women should be seen as the first target populations. It seems that although expanding the educational system might help the state to provide people with more educational options, it is also necessary to ensure that equal opportunities and access to quality education are provided for those from lower socioeconomic backgrounds; otherwise the current situation might cost the government more in the long term because of poor health among disadvantaged groups.